Ictal cerebral perfusion related to EEG in drug resistant focal epilepsy of childhood. Issue 4 (April 1997) - Cross, J H; Boyd, S G; Gordon, I; Harper, A; Neville, B G
Abstract : OBJECTIVES: To evaluate the EEG changes during seizures in children with drug resistant focal epilepsy who demonstrate hypoperfusion at the "seizure focus" interictally, but no perfusion change during the seizure. METHODS: Ictal EEG findings of six children with focal epilepsy who demonstrated hypoperfusion on rCBF SPECT after an interictal injection of (99)Tc(m) HMPAO concordant with the seizure focus, but who did not demonstrate rCBF change after an ictal injection (group 1) were reviewed. These were contrasted with the EEG data of six children matched as closely as possible for age, type of epilepsy, and pathology who did show hyperperfusion at the seizure focus on ictal scan when compared with the interictal study (group 2). RESULTS: The children in group 1 showed slowing of the EEG at the time of the (99)Tc(m) HMPAO injection relative to that seen at the onset of the seizure. Those in group 2 showed rhythmic activity, or sharp waves, or both on EEG at the time of injection. This last change was also seen consistently when the EEG data of a further 13 children who also showed ictal hyperperfusion at the seizure focus were reviewed. CONCLUSION: Ictal rCBF does not invariably increase at the seizure focus in patients with drug resistant focal epilepsy.